PENGARUH PELATIHAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PT. NISSIN KOGYO BATAM - Indra Nanda (LPPM AMIK Citra Buana Indonesia, 2016)
Based on the observations and initial data, the performance of employees of PT. Nissin Kogyo Batam in the last four years tended to decline, seen from the still high number of quality complaints from customers. Predicted poor performance of the employee is due to the lack of employee training, resulting in low job satisfaction. The purpose of this research was to reveal the influence of both variables on job satisfaction and performance. Analysis of the data used is the Path Analysis. The hypothesis of this researchare as follows: training effect on employee job satisfaction of PT. Nissin Kogyo Batam, and training and job satisfaction simultaneously affect the employee satisfaction of PT. Nissin KogyoBatam. The research findings that training is only an impactof 9.1% to job satisfaction, and the influence of training and job satisfaction which directly affects the employee's performance of 39.2% and significant. The remaining 60.8% influenced by other factors.